Historical Entrepreneurship Program Development (Historiopreneurship) in Samarinda City and Kutai Kartanegara - Reza Reza; Vitria Puri Rahayu; Christie Stephanie Piar; Dwi Atmono; Muhammad Rahmatullah; Nurliyana Nurliyana (Educational Studies: Conference Series, 2022)
These ancient mosques, both located in Samarinda and Tenggarong, are relics of the Islamic community in the past where the location around the mosque besides being a center for worship and development of Islamic religion. The existence of ancient relics in the form of old mosques which have cultural and religious values ​​should ideally be preserved to develop Islamic symbols. Apart from that, it can be a place for religious tourism education in East Borneo. The purpose of this research is to identify the potential for historical entrepreneurship in the cities of Samarinda and Tenggarong, as well as to analyze the need for historical entrepreneurship programs in universities in Samarinda and Tenggarong. The research approach uses a qualitative approach. Research using historical methods. Data collection was carried out by observation and interview techniques. The results of the research show that cultural heritage that has historical value can become the religious center of the surrounding community and pave the way to become a center of economic activity that produces an entrepreneurial community. The research findings show that the strategic location of historical places can make the surrounding community more creative in maximizing economic potential in entrepreneurship. The implications of further research are expected to be used to develop entrepreneurship programs in universities based on local wisdom in East Borneo.